Malignant Mesothelioma of the Tunica Vaginalis Testis: A Case Report and Literature Review - Jing-Liang Chen; Yung-Hsiang Hsu (Kaohsiung Journal of Medical Sciences, 2009)
Malignant mesothelioma of the tunica vaginalis testis is a rare but often fatal malignancy. Here, we report one patient with locally advanced disease who has a history of asbestos exposure. We review the literature concerning current management strategies of the disease. Radical surgery plus adjuvant radiotherapy seems to provide the best results.